Blood Lipid Profile of Coturnix coturnix japonica Fed whith Organic Feed and Supplement Curcuma longa - Entin Nur Aetin; Tyas Rini Saraswati; Sri Isdadiyanto (Biosaintifika: Journal of Biology & Biology Education, 2017)
People’s concern about quail egg consumption has triggered the efforts to produce quail eggs with low cholesterol content by using organic feed. Organic feed is one type of feed rations made of mixing organic material. In this study, standard organic feed (rice bran, yellow corn, soybean, and fishmeal) and organic feed containing mackerel, cassava leaves, and turmeric powder was administere to female japanese quail. Organic feed containing mackerel, cassava leaves, and turmeric powder can affect the Japanese quail (Coturnix coturnix japonica L.) lipid profile. This research used experimental methods. Twenty-seven female Japanese quails were divided into 3 treatment groups (PO: commercial feed, P1: standard organic feed, P2: feed containing organic turmeric powder, cassava leaves, and mackerel) for 145 days with 9 repeat. Data obtained were in the form of average daily feed intake and blood lipid profiles of each treatment group. Further data analysis was performed by analysis of variance (ANOVA) followed by Duncan test. The results showed that administration of organic feed containing mackerel, cassava leaves, and turmeric powder can reduce the levels of cholesterol, triglycerides, and LDL but increase the HDL levels in Japanese quail. Supplementation of turmeric powder improve the chemical quality of Japanese quail eggs, so it is good for the development of quail embryos as well as for consumption. It can be concluded that organic feed and turmeric powder supplementation stabilize blood lipid profile and improve the reproduction of Japanese quail egg low cholesterol, so good for the development of embryo quail and for consumption.